2020
DOI: 10.3390/en13225865
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis on the Balancing Hole Design for Magnetic Drive Centrifugal Pumps

Abstract: Balancing holes in single-suction centrifugal pumps are generally applied to attenuate the axial thrust caused by a pressure difference between the front side of a shroud and the rear side of a hub of an impeller. The magnetic drive pump, the subject of this study, has a leak-free airtight structure and an integrated structure of the impeller and inner magnet. To prevent the performance degradation of the magnetic drive caused by heat during operation, complex cooling flow paths connected to balancing holes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Zhao et al 33 and Yan et al 34 studied the effect of variation of wear ring clearances and found that with an increase in the clearance gap, the performance drops. Kim and Yun 35 studied the effect of taking into account the balance holes in the impeller shroud. They observed that the presence of balance holes not only reduced the axial force but also the head developed and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al 33 and Yan et al 34 studied the effect of variation of wear ring clearances and found that with an increase in the clearance gap, the performance drops. Kim and Yun 35 studied the effect of taking into account the balance holes in the impeller shroud. They observed that the presence of balance holes not only reduced the axial force but also the head developed and efficiency.…”
Section: Introductionmentioning
confidence: 99%